EXPLORING TRANSLANGUAGING PRACTICES AS A PEDAGOGICAL STRATEGY IN TEACHING ENGLISH AT VOCATIONAL HIGH SCHOOL - Nafisah Ainiyyah; Yulie Asni; Zulfah Fakhruddin; Abdul Haris Sunubi (e-Journal of ELTS (English Language Teaching Society), 2026)
This study aims to describe the implementation of translanguaging practices by English teachers in vocational high school classrooms and to explore the perceived benefits and challenges of this pedagogical strategy. Utilizing a field-based qualitative descriptive approach, the research was conducted at SMKN 3 Parepare, involving one English teacher and eight students. Data were collected through classroom observations, semi-structured interviews, and document analysis of lesson plans and teaching modules, then analyzed using the Miles and Huberman interaction model. The findings reveal that translanguaging is primarily implemented as a spontaneous, rather than planned, instructional response. It serves crucial functions in classroom management, cognitive scaffolding—particularly in grammar instruction by comparing local languages (Buginese and Indonesian) with English—and facilitating student interaction. The perceived benefits include bridged comprehension, reduced speaking anxiety, and increased student confidence. However, a significant challenge emerged regarding students' limited basic vocabulary, leading to a high risk of dependency on their native languages. These findings imply that educators should adopt a flexible, linguistically inclusive approach rather than strict English-only policies, validating students' multilingual resources as cognitive bridges. Nevertheless, teachers must manage translanguaging systematically to prevent over-reliance on the first language and gradually guide students toward English independence